From Blatter Radical to 7-Substituted 1,3 - Diphenyl-1,4 - Dihydrothiazolo [5′,4′:4,5] Benzo[1,2-e][1,2,4] Triazin-4-yls : Toward Multifunctional Materials - Berezin, Andrey A.; Constantinides, Christos P.; Manoli, Maria; Koutentis, Panayiotis A.; Drouza, Chryssoula (My University, 2012)
A Blatter radical is oxidized to benzotriazin-7(H)-one which after amination and subsequent acyl- and aroylation gives N-(benzotriazin-6-yl) carboxamides that undergo ring closure with P 2S 5 to afford the corresponding thiazolo[5′,4′:4,5]benzo[1,2-e][1,2,4]triazin-4- yls. These highly delocalized radicals are air stable and show good reversible electrochemical behavior. © 2012 American Chemical Society
Keywords: Materials; Roots